METHODS FOR ENHANCING THE CREATIVE COMPETENCE OF STUDENTS IN SPECIALIZED SCHOOLS THROUGH THE INTEGRATION OF MODERN PEDAGOGICAL AND DIGITAL TECHNOLOGIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
In the modern education system, it is of great importance to encourage students to think creatively, solve problems, and generate new ideas. Particularly in specialized schools, it is necessary to prepare students in accordance with contemporary demands and to utilize modern pedagogical technologies and digital resources to enhance their creative competence. This article identifies how teachers can apply modern pedagogical technologies and use digital resources to improve students’ creative abilities. This article highlights the issues of developing students’ creative competence in teaching chemistry in specialized schools. The study analyzes the methodological foundations for integrating modern pedagogical technologies (problem-based learning, project-based learning) and digital tools (VR/AR, artificial intelligence, 3D modeling). The results of the research conducted based on the IMRAD standard demonstrate an improvement in students’ independent thinking and their ability to find solutions in non-standard situations.